Electron energy-loss spectroscopic tomography of FexCo(3−x)O4 impregnated Co3O4 mesoporous particles: unraveling the chemical information in three dimensions. Issue 16 (17th June 2016) - Yedra, L.; Eljarrat, A.; Arenal, R.; López-Conesa, L.; Pellicer, E.; López-Ortega, A.; Estrader, M.; Sort, J.; Baró, M. D.; Estradé, S.; Peiró, F.
Abstract : Electron energy-loss spectroscopy-spectrum image (EELS-SI) tomography is a powerful tool to investigate the three dimensional chemical configuration in nanostructures. Abstract : Electron energy-loss spectroscopy-spectrum image (EELS-SI) tomography is a powerful tool to investigate the three dimensional chemical configuration in nanostructures. Here, we demonstrate, for the first time, the possibility to characterize the spatial distribution of Fe and Co cations in a complex Fe x Co(3− x ) O4 /Co3 O4 ordered mesoporous system. This hybrid material is relevant because of the ferrimagnetic/antiferromagnetic coupling and high surface area. We unambiguously prove that the EELS-SI tomography shows a sufficiently high resolution to simultaneously unravel the pore structure and the chemical signal.